Effects of elicitors of host plant defenses on pear psylla, Cacopsylla pyricola. Issue 3 (3rd October 2015) - Cooper, W. Rodney; Horton, David R.
Abstract: Pear psylla, Cacopsylla pyricola (Foerster) (Hemiptera: Psyllidae), is a key pest of cultivated pear [ Pyrus communis L. (Rosaceae)] in North America and Europe. We examined the effects of foliar applications of three commercially available chemical elicitors of host‐plant defenses — Actigard (acibenzolar‐ S ‐methyl), Employ (harpin protein), and ODC (chitosan) — on survival, development, feeding, and egg laying of C. pyricola . All three defense elicitors reduced the number of nymphs present on pear (cvs. Bartlett or D'Anjou) 30 days after releasing 10 adults on the trees. Choice assays showed that females settled and oviposited on untreated trees more often than on trees treated with any of the three defense elicitors. Results of no‐choice assays confirmed that the effects of Actigard, Employ, and ODC on C. pyricola were due to activation of systemic plant responses that led to reduced oviposition preference and nymph survival. However, results did not provide evidence that plant responses to elicitors led to reduced nymphal feeding rates or development. Results of our laboratory studies suggest that commercial defense elicitors may be useful in the integrated management of pear psylla once the effects of elicitors at an ecological scale are better understood.